RESPON PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) TERHADAP KOMBINASI PUPUK ORGANIK, ANORGANIK DAN MULSA DI LEMBAH PALU - Abdul Rauf, Henry N Barus, MohKholidin (AGROTEKBIS, 2016)
The aim of the study was Â to determine the effectÂ  of organic and inorganic fertilizers combined with mulching on the growth and yield of mustard (Brassica juncea L.). This study used a randomized block design consisted of six treatments.Â  The study was located in Bulu Pountu jaya, Sigi Biromaru, Central Sulawesi and conducted from March â April 2015. The study results showed that the application of organic fertilizer should be accompanied with the inorganic feertilizer to produce better plant growth.Â  The total fresh weight of the mustard plants was 173.88 g increasing to 294.97 g when all treatments were applied simultaneously.Â  Besides, this treatment also resulted in higher plant height,Â  more leaves and large leaf area size.